Strategi Public Relations dalam Mengatasi Reputasi Negatif Perusahaan Umum Daerah Tirta Musi Palembang - Brillian Akbar Algiffari; Taufik Akhyar; Sonia Nurprameswari (LPPM Universitas HKBP Nommensen, 2025)
Perumda Tirta Musi Palembang is facing a reputation crisis triggered by repeated disruptions in the clean water distribution, resulting in more than 268,950 customer complaints in one month as well as massive negative coverage in mass media and social media. This situation demands the implementation of a systematic public relations strategy to restore public trust. This study aims to analyze Perumda Tirta Musi Palembang's public relations strategy in addressing negative reputation in the community and to describe the public relations challenges faced by Perumda Tirta Musi Palembang in managing negative issues in the community. This study uses Howard Chase's Issue Management Theory as the main analytical framework. The research method used is qualitative with a case study approach. The research results show that Perumda Tirta Musi's public relations strategy is carried out through five integrated stages of the Issue Management Theory, namely issue identification through daily social media monitoring and call center data classification, issue analysis through internal cross-division verification, strategy selection in the form of a maximum 15-minute response, educational content, press releases, field documentation, tanker water distribution, and dissemination of information through RT/RW networks, implementation with a standard resolution of 1x24 hours for distribution disruptions and three days for general complaints, and evaluation through sentiment monitoring and annual customer satisfaction surveys. The main challenges include limitations in human resources, internal coordination obstacles, discrepancies between estimated normalization times and field realities, as well as limitations in communication technology infrastructure. Although the implemented strategy has been running as a fully integrated cycle, Long-term restoration of public trust remains a major challenge that requires consistent performance and ongoing communication.